GGR Biennial Critical Review: Analytical Developments Since 2012 - Wiedenbeck, M.; Bedard, L.; Bugoi, R.; Horan, M.; Linge, Kathryn; Merchel, S.; Morales, L.; Savard, D.; Souders, A.K.; Sylvester, P. (Wiley-Blackwell Publishing, 2014)
Advances in the chemical, crystallographic and isotopic characterisation of geological and environmental materials can often be ascribed to technological improvements in analytical hardware or to innovative approaches to data acquisition and/or its interpretation. This biennial review addresses key laboratory methods that form much of the foundation for analytical geochemistry; again this contribution is presented as a compendium of laboratory techniques. We highlight advances that have appeared since January 2012 and that are of particular significance for the chemical and isotopic characterisation of geomaterials. Prominent scientists from the selected analytical fields present publications they judge to be particular noteworthy, providing background information about the method and assessing where further opportunities might be anticipated. In addition to well established technologies such as thermal ionisation massspectrometry and plasma emission spectroscopy, this publication also presents new or rapidly growing methods such as electron backscattered diffraction analysis and atom probe tomography – a very sensitive method providing atomic scale information.